Differential Invariants of Two Affine Curve Families - Yasemin Sağıroğlu; Demet Aydemir; Uğur Gözütok (IndoMS, 2019)
This paper examines the affine differential invariants of two curves. The equivalence of two curves is obtained by using these invariants according to the affine group. In addition, obtained differential invariants will be shown to be the minimal system of the generators.